Adult mortality and antiretroviral treatment roll-out in rural KwaZulu-Natal, South Africa - Abraham J Herbst; Graham S Cooke; Till Bärnighausen; Angelique KanyKany; Frank Tanser; Marie-Louise Newell (The World Health Organization, 2009)
OBJECTIVE: To investigate trends in adult mortality in a population serviced by a public-sector antiretroviral therapy (ART) programme in rural South Africa using a demographic surveillance system. METHODS: Verbal autopsies were conducted for all 7930 deaths observed between January 2000 and December 2006 in a demographic surveillance population of 74 500 in the Umkhanyakude district of northern KwaZulu-Natal province, South Africa. Age-standardized mortality rate ratios (SMRRs) were calculated for adults aged 25 to 49 years, the group most affected by HIV, for the 2 years before 2004 and the 3 subsequent years, during which ART had been available. FINDINGS: Between 2002-2003 (the period before ART) and 2004-2006 (the period after ART), HIV-related age-standardized mortality declined significantly, from 22.52 to 17.58 per 1000 person-years in women 25-49 years of age (P < 0.001; SMRR: 0.780; 95% confidence interval, CI: 0.691-0.881), and from 26.46 to 18.68 per 1000 person-years in men 25-49 years of age (P < 0.001; SMRR: 0.706; 95% CI: 0.615-0.811). On sensitivity analysis the results were robust to the possible effect of misclassification of HIV-related deaths. CONCLUSION: Overall population mortality and HIV-related adult mortality declined significantly following ART roll-out in a community with a high prevalence of HIV infection. A clear public health message of the benefits of treatment, as revealed by these findings, should be part of a multi-faceted strategy to encourage people to find out their HIV serostatus and seek care.